Nanocellulose hydrogel as well as preparation method and application thereof

Through the design of the bi-crosslinked cellulose hydrogel, combined with chemical and physical crosslinking networks, the performance problems of conductive hydrogels at extreme temperatures are solved, and high toughness, anti-freeze and dehydration are achieved, suitable for flexibility Wearable electronic devices.

CN119285859APending Publication Date: 2025-01-10DALIAN JIAOTONG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411403291.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing conductive hydrogels freeze or dehydrate at extreme temperatures, resulting in impaired electrical conductivity and mechanical properties, and the poor mechanical properties of traditional hydrogels limit their application in flexible wearable electronic devices.

Method used

Using a bi-crosslinked cellulose hydrogel, through the combination of chemical crosslinking network and physical crosslinking network, cellulose nanofibers and ionic components are introduced to form a stable network structure, and organic solvents are used as dispersion medium to enhance the gel's Resistant to freezing, dehydration and mechanical properties.

Benefits of technology

It achieves anti-freeze at -60°C and anti-dehydration capacity of room temperature for 40 days, maintains excellent mechanical properties and ionic conductivity, improves the toughness and fracture strength of the gel, and reduces the brittleness of the hydrogel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285859A_ABST
    Figure CN119285859A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of cellulose hydrogel materials, and particularly relates to nano-cellulose hydrogel and a preparation method and application thereof, and the structure of the nano-cellulose hydrogel is composed of a chemical cross-linked network and a physical cross-linked network; the chemical cross-linked network is a covalent cross-linked chemical cross-linked network structure formed by chemical cross-linking of an acrylamide derivative or an acrylic acid derivative; according to the physical cross-linked network, cellulose nanofibers are introduced into the chemical cross-linked network to serve as a physical cross-linking agent, a solvent and an ionic component are introduced, reversible physical interaction is formed between the physical cross-linking agent and a polymer chain, and the ionic component is dissolved in the solvent to replace moisture in the gel material, so that the physical cross-linked network is formed. The bi-crosslinked cellulose hydrogel has the advantages that the bi-crosslinked cellulose hydrogel is prepared from cellulose nanofibers, non-covalent connection and ion component rivet hydrogen bond connection are carried out on the cellulose nanofibers, the bi-crosslinked cellulose hydrogel is rich in non-covalent interaction including hydrogen bond, ion and coordinate bond interaction, and accordingly the ionic hydrogel is ideal in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cellulose hydrogel materials, and specifically relates to a nano cellulose hydrogel and a preparation method and application thereof. Background Art

[0002] With the continuous progress and development of science and technology and the advent of the intelligent era, flexible wearable electronic devices have received widespread attention due to their excellent electrical properties. Conductive hydrogels show broad application prospects in various portable smart wearable electronic products and flexible sensors due to their high flexibility, stretchability, adjustable mechanical properties and excellent conductivity. Among them, hydrophilic three-dimensional network structure hydrogels are ideal candidate materials for flexible and wearable sensors due to their good viscoelasticity, transparency and biocompatibility. However, most traditional hydrogels generally have the problem of poor mechanical properties, mainly due to the uneven cross-linking structure and the lack of effective energy dissipation mechanism, which seriously limits their further practical applications.

[0003] In recent years, researchers have made many attempts to improve the mechanical properties of hydrogels, including double network structures, topological slide ring gels, tetra-PEG gels, and nanocomposite (NC) hydrogels. Among them, NC hydrogels are considered to be the preferred solution for achieving mechanical property enhancement by preventing the formation and expansion of cracks.

[0004] However, the dispersion medium in current conductive hydrogels is water, which will inevitably freeze or evaporate rapidly at extreme temperatures, causing serious damage to its conductivity and mechanical properties. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a nanocellulose hydrogel and a preparation method and application thereof. The hydrogel of the present invention is a double-crosslinked cellulose hydrogel. These double-crosslinked cellulose hydrogels have rich non-covalent interactions, including hydrogen bonds, ions and coordination bonds, which make the ionic hydrogel have ideal properties, including antifreeze (-60°C) and long-term anti-dehydration ability (40d in room temperature environment), reliable adhesion, excellent mechanical properties and outstanding ionic conductivity.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A nanocellulose hydrogel, wherein the structure of the nanocellulose hydrogel comprises a chemical cross-linking network, a physical cross-linking network and a dispersion medium;

[0008] The chemical cross-linking network is formed by chemical cross-linking between acrylamide derivative or acrylic acid derivative monomer chains using a chemical cross-linking agent under the action of an initiator;

[0009] The physically cross-linked network includes a structure formed by introducing cellulose nanofibers and a structure formed by introducing ionic components. The structure formed by introducing cellulose nanofibers is that cellulose nanofibers are introduced into the chemically cross-linked network as physical cross-linking agents, and reversible physical interactions are formed between the physical cross-linking agents and polymer chains; the structure formed by introducing ionic components is that non-covalent connections occur between the ionic components and the cellulose nanofibers, and the ionic components are connected by rivet hydrogen bonds;

[0010] The dispersion medium is dispersed in the chemical cross-linking network and the physical cross-linking network, and the dispersion medium is an organic solvent.

[0011] The present invention uses cellulose nanofibers as physical crosslinkers, and uses chemical crosslinkers to introduce covalent interactions in polymer chains to give the gel a stable structure and cohesion. By forming covalent bonds between polymer chains, a robust and stable network is established, thereby enhancing the structural integrity and mechanics of the gel. However, with the increase of covalent bonds in the gel, the polymer chains become harder and have a worse ability to deform under stress, resulting in a brittle structure and loss of elasticity and flexibility; therefore, cellulose nanofibers are introduced into the gel as green physical crosslinkers to achieve high toughness, fracture strength and stretchability of the gel. Physical crosslinking involves the formation of reversible physical interactions between polymer chains, such as ionic interactions, hydrogen bonds and coordination, which provide energy dissipation and enable stress to be transmitted through the polymer chains. In addition, the surface of cellulose nanofibers also has negative surface carboxylic acid groups, which can improve the ionic conductivity of the gel network.

[0012] Another object of the present invention is to provide a method for preparing the above-mentioned cellulose nanofiber hydrogel, comprising the following steps:

[0013] preparing a cellulose nanofiber dispersion, using the cellulose nanofiber dispersion as a physical cross-linking agent;

[0014] The acrylamide derivative or acrylic acid derivative monomer, chemical crosslinking agent, initiator, and ionic component are dissolved in a binary solvent composed of water and organic matter, and then a cellulose nanofiber dispersion is added thereto to obtain a homogeneous precursor solution, and the homogeneous precursor solution is polymerized under ultraviolet light or heating conditions to obtain a nanocellulose hydrogel.

[0015] The cellulose nanofiber hydrogel can also be prepared by the following method:

[0016] preparing a cellulose nanofiber dispersion, using the cellulose nanofiber dispersion as a physical cross-linking agent;

[0017] The acrylamide derivative or acrylic acid derivative monomer, a chemical crosslinking agent and an initiator are dissolved in water to obtain a mixed solution, and then a cellulose nanofiber dispersion is added to the mixed solution, and then a uniform mixture is formed under ice bath conditions, and the mixture is formed into a covalently crosslinked nanocomposite gel under a nitrogen atmosphere; the covalently crosslinked nanocomposite gel is immersed in a binary solvent composed of ionic components, water and organic matter to obtain a nanocellulose hydrogel.

[0018] In a preferred embodiment of the present invention, the acrylamide derivative or acrylic acid derivative monomer is one of acrylamide, acrylic acid, N-isopropylacrylamide, hydroxyethyl methacrylate, and polyethylene glycol diacrylate, and the initiator is one of ammonium persulfate, potassium persulfate, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, and 2-hydroxy-2-methylpropiophenone.

[0019] In a preferred embodiment of the present invention, the ion component is Ca 2+ , Fe 3+ 、Al 3+ , Cu 2+ 、Zn 2+ 、Na + One of a kind.

[0020] In a preferred embodiment of the present invention, the organic solvent is one of sorbitol, glycerol, proline, betaine, and 1,3-propylene glycol, and in the binary solvent, the mass ratio of the organic solvent to water is 2 to 3:1.

[0021] In a preferred embodiment of the present invention, the mass ratio of acrylamide derivative or acrylic acid derivative monomer, crosslinking agent, and initiator is 300-600:0.001-0.1:10-40.

[0022] In a preferred embodiment of the present invention, when the solvent is distilled water, the mass ratio of the cellulose nanofiber dispersion to the mixed solution is 1 to 3:1.

[0023] In a preferred embodiment of the present invention, the method for preparing the cellulose nanofiber dispersion comprises the following steps:

[0024] The original cellulose is soaked with an acid catalyst, then broken up, and the reaction is terminated with distilled water to obtain a cellulose raw material;

[0025] The cellulose raw material is filtered and dehydrated until the moisture content reaches 2% to 5%, and stored at 0 to 4° C. before use to obtain incompletely dried cellulose; if the solvent is only a hydrogel system of distilled water, a binary solvent is used to soak for a specific time.

[0026] The incompletely dried cellulose is suspended in distilled water containing TEMPO and sodium bromide, and then ammonium hypochlorite is added to carry out a TEMPO-mediated oxidation reaction, and NaOH is added simultaneously to adjust the pH to 9.7-10.3, and the reaction is completed after the pH is stabilized; in the distilled water containing TEMPO and sodium bromide, the molar ratio of TEMPO to sodium bromide is 0.1-0.2:1-2, and the molar ratio of the added sodium hypochlorite to TEMPO is 1.5-10:0.1-0.2.

[0027] After oxidation, ethanol was added to quench the reaction, and HCl was added to adjust the pH of the reaction to 7. Finally, the TEMPO oxidation product was filtered and washed;

[0028] The washed product is then dispersed in water and centrifuged to remove the precipitate and collect the supernatant, which is then subjected to mechanical defibrillation to obtain a uniformly dispersed TEMPO-oxidized cellulose nanofiber dispersion.

[0029] In a preferred embodiment of the present invention, the acid catalyst is HCl solution, the mass volume ratio of the original fiber to the HCl solution is 1 g:15-20 mL, and the concentration of the HCl solution is 4-6M.

[0030] In a preferred embodiment of the present invention, the mass ratio of monomer, crosslinking agent and initiator is 300-600:0.001-0.1:10-40, and the ion component is Ca 2+ , Fe 3+ 、Al 3+ , Cu 2+ 、Zn 2+ 、Na + The carbon nanofiller is one or more of carbon black, graphene, carbon nanotubes, and carbon fibers.

[0031] In a preferred embodiment of the present invention, the solvent is distilled water or a binary organic solvent based on distilled water.

[0032] In a preferred embodiment of the present invention, the TEMPO oxidation time is 4 to 8 hours, during which a uniform stirring rate of 500 to 700 rpm is maintained.

[0033] In a preferred embodiment of the present invention, the mechanical defibrillation should be high-pressure homogenization or high-speed shearing or ultrasonic shearing crushing defibrillation to ensure the particle size of the cellulose.

[0034] The defibrillation conditions of the high-pressure homogenizer used are: slurry concentration 0.5% to 2.0%, homogenization pressure 600 bar to 1000 bar, and homogenization times 5 to 10 times.

[0035] The high-speed shear defibrillation conditions used are: slurry concentration 0.5% to 2.0%, shear rate 30000 to 50000 rpm, time 1 to 60 min;

[0036] The ultrasonic shearing and crushing defibrillation conditions adopted are: slurry concentration 0.5% to 2.0%, ultrasonic power 600 to 800W, and time 30 to 60 minutes.

[0037] In a preferred embodiment of the present invention, the organic solvent is one of sorbitol, glycerol, proline, betaine, and 1,3-propylene glycol.

[0038] In a preferred embodiment of the present invention, the mass ratio of the cellulose nanofiber dispersion to the mixed solvent is 1 to 3:1.

[0039] In a preferred embodiment of the present invention, the monomer includes one of acrylamide (AM), acrylic acid (AA), N-isopropylacrylamide (NIPAM), hydroxyethyl methacrylate (HEMA), and polyethylene glycol diacrylate (PEGDA), and the chemical crosslinking agent is one of divinylbenzene, diisocyanate, and N,N′-methylenebisacrylamide.

[0040] In a preferred embodiment of the present invention, the initiator includes one of ammonium persulfate (APS), potassium persulfate (KPS) Irgacure 2959, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone (IR2959), and 2-hydroxy-2-methylpropiophenone (1173).

[0041] Cellulose nanofibers act as physical crosslinkers to enhance the mechanical properties of the hydrogel while maintaining the elasticity of the internal network of the polymer, thereby mitigating the loss of adhesion, so the dosage of chemical crosslinkers such as divinylbenzene, diisocyanate, N,N′-methylenebisacrylamide (MBA), etc. can be reduced.

[0042] In a preferred embodiment of the present invention, the raw fiber includes one or more of cotton pulp, pine pulp, coniferous wood pulp board, hardwood wood pulp board and wheat straw.

[0043] The preparation strategy of the hydrogel described in the present invention not only includes cellulose nanofibers prepared by TEMTO oxidation, but is also applicable to sodium cellulose fibers prepared by organic solvent systems, aqueous solvent systems, ionic liquid systems, and the like.

[0044] The third object of the present invention is to provide an application of the nanocellulose hydrogel described above in the fields of bioelectrodes, wearable devices, human motion detection and electromagnetic wave absorption.

[0045] Compared with inorganic nanoparticles, cellulose nanofibers (CNF) have an extremely high aspect ratio, which is conducive to the formation of strong physical entanglement and cohesive network in the gel matrix, giving the gel structure mechanical stability and better compatibility. On the other hand, CNF-reinforced hydrogel materials usually have a nanoporous structure, which can adsorb more ions, provide more space as channels for ion migration, promote ion migration, and thus significantly improve the ionic conductivity of the composite hydrogel.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] 1. The present invention uses cellulose nanofibers as physical crosslinkers, and uses chemical crosslinkers to introduce covalent interactions in polymer chains to give the gel a stable structure and cohesion. By forming covalent bonds between polymer chains, a robust and stable network is established, thereby enhancing the structural integrity and mechanical properties of the gel. However, with the increase of covalent bonds in the gel, the polymer chain becomes harder and has a worse ability to deform under stress, resulting in a brittle structure and loss of elasticity and flexibility; therefore, cellulose nanofibers are introduced into the gel as green physical crosslinkers to achieve high toughness, fracture strength and stretchability of the gel. Physical crosslinking involves the formation of reversible physical interactions between polymer chains, such as ionic interactions, hydrogen bonds and coordination, which provide energy dissipation and enable stress to be transmitted through polymer chains. The dispersion medium is an organic solvent, which improves the antifreeze and anti-dehydration properties of the hydrogel. In addition, the surface of the cellulose nanofibers also has negative surface carboxylic acid groups, which can improve the ionic conductivity of the gel network.

[0048] 2. When the ambient temperature is below the freezing point, the water molecules in the hydrogel network tend to be inevitably frozen. It not only limits their ion transport capacity, but also makes them hard and fragile, which severely limits their application in the low temperature range. In addition, since the water in the hydrogel inevitably evaporates under ambient conditions, the performance of the hydrogel will significantly decrease over time, and high temperature will aggravate the dehydration of the hydrogel, eventually leading to a complete loss of function. In the present invention, the alternating introduction of binary solvents and ionic components, the ionic components are dissolved in the binary solvent, replace the water in the gel material, and non-covalently bonded with cellulose, and the ionic components are rivet hydrogen bonded, which can improve the antifreeze and anti-dehydration properties of hydrogels working in extreme environments, and have excellent ionic conductivity.

[0049] 3. Petroleum-derived synthetic polymers are very popular and play an important role in human daily life because they can be customized to meet the daily needs of life. Given the inherent non-degradability and dependence of these polymers on petroleum resources, there is a serious long-term impact on the environment, and there is an urgent need to develop alternative and sustainable innovative materials. Cellulose, as an inexhaustible renewable resource in nature, is the oldest and most abundant natural polymer on earth. Due to its renewability, availability, non-toxicity, low cost, environmental friendliness and biodegradability, it is a promising alternative to petroleum-derived synthetic polymers. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a physical photograph of the double cross-linked cellulose hydrogel prepared in Example 1 of the present invention.

[0051] Figure 2 This is a photograph of the double cross-linked cellulose hydrogel prepared in Example 1 of the present invention after violent compression.

[0052] Figure 3 This is a photograph of the double-crosslinked cellulose hydrogel prepared in Example 1 of the present invention after violent stretching.

[0053] Figure 4 This is the Nyquist curve of the double-crosslinked cellulose hydrogel prepared in Example 1 of the present invention at room temperature and -40°C, wherein the inset is a CV curve diagram. DETAILED DESCRIPTION

[0054] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0056] Example 1

[0057] A method for preparing a nanocellulose hydrogel comprises the following steps:

[0058] (1) A certain amount of cotton linter cellulose was reacted with a dilute HCl solution at a solid-liquid ratio of 1:20 at 70°C for 90 minutes, and then the mixture was broken up and distilled water was added to terminate the reaction.

[0059] (2) After standing overnight, the supernatant was discarded, and the sample was repeatedly washed with distilled water until the pH value was close to neutral. The viscous substance was then filtered and dried until the water content in the sample reached 4%, thereby obtaining incompletely dried cellulose.

[0060] (3) An appropriate amount of partially dried cellulose was weighed and suspended in water (150 mL) containing TEMPO (0.16 mmol) and sodium bromide (2 mol). Then, 5.0 mmol of 11.9% sodium hypochlorite (NaClO) was added to start the TEMPO-mediated oxidation reaction. During this period, NaOH was continuously added to adjust the pH value of the solution to 10. When no further pH drop was observed, the reaction was completed.

[0061] (4) After oxidation, the reaction was quenched by adding an appropriate amount of ethanol, and the pH of the reaction was adjusted to 7 by adding 0.5 M HCl. The TEMPO-oxidized product was then filtered and thoroughly washed with water, and the washed product was then redispersed in water. The dispersion was then centrifuged at high speed to remove the precipitate and collect the upper dispersion. Finally, the collected supernatant was defibrillated at 800 W to obtain a uniformly dispersed TEMPO-oxidized cellulose nanofiber (CNF) dispersion.

[0062] (5) Under nitrogen purge, acrylamide (AM), N, N'-methylenebisacrylamide (MBA), AlCl3 and ammonium persulfate (APS) were completely dissolved in the binary solvent of betaine / water, the mass ratio of acrylic acid (AA), N, N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) was 500:0.05:20, and the mass ratio of betaine to water was 3:1 in the binary solvent of betaine and water. Then, CNF dispersion was added under continuous stirring to prepare a homogeneous precursor solution, which was polymerized in an oven at 70 °C for 60 min to obtain a hydrogel. In order to remove surface residues, the hydrogel was immersed in excess distilled water and the apparent moisture was dried at room temperature.

[0063] Example 2

[0064] A method for preparing a nanocellulose hydrogel comprises the following steps:

[0065] (1) A certain mass of softwood pulp cellulose was reacted with a dilute HCl solution at a solid-liquid ratio of 1:20 at 60°C for 60 minutes, and then the mixture was broken up. Finally, an excess amount of distilled water was added to terminate the reaction.

[0066] (2) After standing overnight, the supernatant was discarded and the sample was repeatedly washed with distilled water until the pH was close to neutral. The viscous substance was then filtered and dried until the water content in the sample reached 5%.

[0067] (3) Weigh an appropriate amount of partially dried cellulose and suspend it in water (100 mL) containing TEMPO (0.16 mmol) and sodium bromide (2 mmol). Then, add 5 mmol of 11.9% sodium hypochlorite (NaClO) to start the TEMPO-mediated oxidation reaction; during this period, NaOH is continuously added to adjust the pH value of the solution to 9.7. When no further pH drop is observed, the reaction is completed.

[0068] (4) After oxidation, the reaction was quenched by adding an appropriate amount of ethanol, and the pH of the reaction was adjusted to 7 by adding 0.5M HCl. Finally, the TEMPO oxidation product was filtered and washed thoroughly with water. The washed product was then redispersed in water. Then, the dispersion was centrifuged at high speed, the precipitate was removed, and the upper dispersion was collected. Finally, the collected supernatant was defibrillated at a stirring rate of 35,000 rpm to obtain a uniformly dispersed TEMPO-oxidized cellulose nanofiber (CNF) dispersion.

[0069] (5) Acrylic acid (AA), N, N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) were completely dissolved in water to obtain a mixed solution, and then CNF dispersion was added to the mixed solution, wherein the mass ratio of acrylic acid (AA), N, N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) was 300:0.001:10, and the mass ratio of CNF dispersion to mixed solution was 2:1, and the mixture was vigorously stirred for 2 h, and then ultrasonicated (300 W) in an ice-water bath for 10 min to form a uniform mixture. The mixture was poured into a PTFE mold at 50 °C under a nitrogen atmosphere for 2 h to obtain a covalently cross-linked nanocomposite gel (NC gel). Then, the obtained NC gel was immersed in a mixed solution containing 3 mol / L CaCl2 and a binary solvent with a mass ratio of sorbitol to H2O of 2:1 at room temperature to form an organogel. In order to remove surface residues, the hydrogel was immersed in excess distilled water and the apparent moisture was dried at room temperature.

[0070] Example 3

[0071] A method for preparing a nanocellulose hydrogel comprises the following steps:

[0072] (1) An appropriate amount of partially dried wheat straw cellulose was weighed and suspended in water (100 mL) containing TEMPO (0.16 mmol) and sodium bromide (2 mmol). Then, 5 mmol of 11.9% sodium hypochlorite (NaClO) was added to start the TEMPO-mediated oxidation reaction; during the process, NaOH was continuously added to adjust the pH value of the solution to 10.3. When no further pH drop was observed, the reaction was completed.

[0073] (2) After oxidation, the reaction was quenched by adding an appropriate amount of ethanol and the pH of the reaction was adjusted to 7 by adding 0.5 M HCl.

[0074] (3) Finally, the TEMPO-oxidized product was filtered and thoroughly washed with water and stored at 4°C, and then the washed product was redispersed in water. Then, the dispersion was centrifuged at high speed, and the precipitate was removed to collect the upper dispersion. Finally, the collected supernatant was defibrillated at a stirring rate of 35,000 rpm to obtain a uniformly dispersed TEMPO-oxidized cellulose nanofiber (CNF) dispersion.

[0075] (4) Acrylic acid (AA), N, N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) were completely dissolved in water to obtain a mixed solution, and then CNF dispersion was added to the mixed solution, wherein the mass ratio of acrylic acid (AA), N, N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) was 600:0.1:40, and the mass ratio of CNF dispersion to mixed solution was 2:1, and the mixture was vigorously stirred for 2 hours, and then ultrasonicated (300W) in an ice water bath for 10 minutes to form a uniform mixture. The mixture was poured into a mold at 70°C under a nitrogen atmosphere for 4 hours to obtain a covalently cross-linked nanocomposite gel (NC gel). Then, the obtained NC gel was immersed in a mixed solution containing 5 mol / L ZnCl2 and a binary solvent with a mass ratio of glycerol to H2O of 3:1 at room temperature to form an organogel. In order to remove surface residues, the hydrogel was immersed in excess distilled water and the apparent moisture was dried at room temperature.

[0076] Results Analysis

[0077] Figure 1 This is a physical photo of the double cross-linked cellulose hydrogel prepared in Example 1 of the present invention; Figure 2 This is a photo of the double cross-linked cellulose hydrogel prepared in Example 1 of the present invention after violent compression; Figure 3 This is a real photo of the double-cross-linked cellulose hydrogel prepared in Example 1 of the present invention after violent stretching; it can be seen that the cellulose hydrogel has extremely high light transmittance and will not break or break when subjected to large instantaneous deformation, which can achieve high toughness, fracture strength and stretchability of the gel and is suitable for various working conditions.

[0078] The Nyquist curve and CV curve of the double cross-linked cellulose hydrogel prepared in Example 1 of the present invention at room temperature and -40°C, wherein the inset is the CV curve, as shown in FIG. Figure 4 As shown in the figure, the gel exhibits high ionic conductivity, and the resistance of the fabricated solid-state supercapacitor only increases from 5.4 to 53.7Ω when the operating temperature drops from 30°C to -40°C. The low resistance of the device facilitates the transport of ions and ensures that the prepared hydrogel has excellent electrochemical performance. In addition, within the entire temperature range of -40 to 30°C, at 50mV S - ( Figure 4 ) scan rate, the quasi-rectangular shape of the CV loop remains unchanged, indicating the ultra-wide operating temperature range of the hydrogel. The loop area in the cyclic voltammetry curve increases with the increase of the operating temperature ( Figure 4 ), illustrating the increase in charge storage of SSCs.

[0079] In summary, the present invention uses cellulose nanofibers as physical crosslinkers, uses chemical crosslinkers to introduce covalent interactions in polymer chains to give the gel a stable structure and cohesion, and establishes a robust and stable network by forming covalent bonds between polymer chains, thereby enhancing the structural integrity and mechanics of the gel. However, with the increase of covalent bonds in the gel, the polymer chain becomes harder and has a worse ability to deform under stress, resulting in a brittle structure and loss of elasticity and flexibility. Introducing cellulose nanofibers as green physical crosslinkers in the gel can achieve high toughness, fracture strength and stretchability of the gel. Physical crosslinking involves the formation of reversible physical interactions between polymer chains, such as ionic interactions, hydrogen bonds and coordination, providing energy dissipation and enabling stress to be transmitted through the polymer chains. In addition, the surface of the cellulose nanofibers also has negative surface carboxylic acid groups, which can improve the ionic conductivity of the gel network.

[0080] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0081] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A nanocellulose hydrogel, characterized in that The structure of the nanocellulose hydrogel includes a chemical cross-linking network, a physical cross-linking network and a dispersion medium; The chemical cross-linking network is formed by chemical cross-linking between acrylamide derivative or acrylic acid derivative monomer chains using a chemical cross-linking agent under the action of an initiator; The physically cross-linked network includes a structure formed by introducing cellulose nanofibers and a structure formed by introducing ionic components. The structure formed by introducing cellulose nanofibers is that cellulose nanofibers are introduced into the chemically cross-linked network as physical cross-linking agents, and reversible physical interactions are formed between the physical cross-linking agents and polymer chains in the chemically cross-linked network; the structure formed by introducing ionic components is that non-covalent connections occur between the ionic components and the cellulose nanofibers, and the ionic components are connected by rivet hydrogen bonds; The dispersion medium is dispersed in the chemical cross-linking network and the physical cross-linking network, and the dispersion medium is an organic solvent.

2. A method for preparing the nanocellulose hydrogel according to claim 1, characterized in that: The following steps are involved: preparing a cellulose nanofiber dispersion, using the cellulose nanofiber dispersion as a physical cross-linking agent; The acrylamide derivative or acrylic acid derivative monomer, chemical crosslinking agent, initiator, and ionic component are dissolved in a binary solvent composed of water and organic matter, and then a cellulose nanofiber dispersion is added thereto to obtain a homogeneous precursor solution, and the homogeneous precursor solution is polymerized under ultraviolet light or heating conditions to obtain a nanocellulose hydrogel.

3. A method for preparing the nanocellulose hydrogel according to claim 1, characterized in that: preparing a cellulose nanofiber dispersion, using the cellulose nanofiber dispersion as a physical cross-linking agent; The acrylamide derivative or acrylic acid derivative monomer, a chemical crosslinking agent and an initiator are dissolved in water to obtain a mixed solution, and then a cellulose nanofiber dispersion is added to the mixed solution, and then a uniform mixture is formed under ice bath conditions, and the mixture is formed into a covalently crosslinked nanocomposite gel under a nitrogen atmosphere; the covalently crosslinked nanocomposite gel is immersed in a binary solvent composed of ionic components, water and organic matter to obtain a nanocellulose hydrogel.

4. The method for preparing the nanocellulose hydrogel according to claim 2 or 3, characterized in that: The ion component is Ca 2+ , Fe 3+ 、Al 3+ , Cu 2+ 、Zn 2+ 、Na + The organic solvent is one of sorbitol, glycerol, proline, betaine, and 1,3-propylene glycol. In the binary solvent, the mass ratio of the organic solvent to water is 2 to 3:

1.

5. The method for preparing the nanocellulose hydrogel according to claim 2 or 3, characterized in that: The mass ratio of acrylamide derivative or acrylic acid derivative monomer, chemical crosslinking agent and initiator is 300-600:0.001-0.1:10-40.

6. The method for preparing the nanocellulose hydrogel according to claim 3, characterized in that: The mass ratio of the cellulose nanofiber dispersion to the mixed solution is 1 to 3:

1.

7. The method for preparing the nanocellulose hydrogel according to claim 2 or 3, characterized in that: The preparation method of the cellulose nanofiber dispersion comprises the following steps: The original cellulose is soaked with an acid catalyst and then broken up to obtain a cellulose raw material; Filtering and dehydrating the cellulose raw material until the moisture content reaches 2% to 5% to obtain incompletely dried cellulose; The partially dried cellulose is suspended in water containing TEMPO and sodium bromide, and then ammonium hypochlorite is added to carry out a TEMPO-mediated oxidation reaction. At the same time, NaOH is added to adjust the pH to 9.7-10.

3. When the pH is stable, the reaction is completed. Ethanol was added to quench the reaction, and HCl was added to adjust the pH to 7. Finally, the TEMPO oxidation product was filtered and washed, and then the washed product was dispersed in water and centrifuged to remove the precipitate and collect the supernatant. The supernatant was mechanically defibrillated to obtain a uniformly dispersed TEMPO-oxidized cellulose nanofiber dispersion.

8. The method for preparing the nanocellulose hydrogel according to claim 7, characterized in that: The raw fibers include one or more of cotton pulp, pine pulp, coniferous wood pulp board, broadleaf wood pulp board and wheat straw.

9. The method for preparing the nanocellulose hydrogel according to claim 7, characterized in that: The acid catalyst is HCl solution, the mass volume ratio of the original fiber to the HCl solution is 1g:15-20mL, the concentration of the HCl solution is 4-6M, and the molar ratio of TEMPO, sodium bromide and sodium hypochlorite is 0.1-0.2:1-2:1.5-10.

10. An application of the nanocellulose hydrogel according to claim 1 in the fields of bioelectrodes, wearable devices, human motion detection and electromagnetic wave absorption.